2022
DOI: 10.3390/su142215053
|View full text |Cite
|
Sign up to set email alerts
|

Can the Resource Curse for Well-Being Be Morphed into a Blessing? Investigating the Moderating Role of Environmental Quality, Governance, and Human Capital

Abstract: One of the most pressing global concerns is ensuring high levels of human well-being without overburdening natural resources. The impact of natural resource abundance on the economy’s monetary dimensions has long been controversial, with researchers debating whether it is a blessing or a curse. Recently, focus has shifted to its impact on non-monetary attributes (i.e., human well-being), with conflicting empirical evidence with respect to existence of the resource curse. However, studies on the indirect impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Moreover, the study conducted by Elmassah and Hassanein (2022) found that HC and resources positively impacted EQ, employing a similar methodology. However, it was observed that growth exhibited a negative correlation with the ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Moreover, the study conducted by Elmassah and Hassanein (2022) found that HC and resources positively impacted EQ, employing a similar methodology. However, it was observed that growth exhibited a negative correlation with the ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In addition, the results reveal that use of renewal energy reduces the negative effect of environmental degradation on life satisfaction. In another study, Elmassah and Hassanein (2022) found that natural resources abundance have negative link with human development. these findings support the notion of "resource curse".…”
Section: Literature Reviewmentioning
confidence: 97%
“…One of the present compelling global concerns is ensuring high levels of human wellbeing without overburdening natural resources; moreover, recently, the focus has shifted towards nonmonetary attributes, i.e., human well-being [11]. So, a continuous growing interest in quality of life and well-being indicators is arising, going beyond gross domestic product (GDP), due to the recognition that the GDP represents solely an economic indicator that shows a partial perspective of the different facets of people's lives [12].…”
Section: Introductionmentioning
confidence: 99%